Tonsättaren-klarinettisten Bernhard Crusell som välgörare i Sverige i början av 1800-talet - Palkisto Janne (Svenska samfundet för musikforskning, 2022)
The philanthropic and charity work of composer and clarinetist Bernhard Crusell (1775–1838) at the beginning of the 19th century
Bernhard Crusell (1775–1838) is a central figure in the music history of both Finland and Sweden. He was born in Uusikaupunki, Finland, and moved in 1791 to Stockholm, where he soon became a leading exponent of the clarinet. During his early professional life, Crusell played in charity concerts to raise funds for an orphanage as well as for the victims of a great fire that happened in the Finnish town of Pori. Two decades later, he established a pension fund for widows and orphans of Linköping’s military musicians. Furthermore, at the end of his career he organized a charity concert and played for the locals and spa guests of the town of Strömstad. The concert proved to be a success and Crusell donated the resulting profits to establish a new foundation, which provided holidays and medical care for poor people every summer.
Crusell’s long-standing philanthropic and charity work is one of the most important elements of his biography that up until now has been ignored. This reflects the general tendency of music historians to think of musicians as being separate from society. However, engaging in charity work was a central activity for any musician living in the 19th century, and this work had a lasting impact on their reputations well beyond their lifetimes.